Exomod: A Python Library for Exoplanet Transit Light Curve Fitting and Stacking with Background Simulation and Optimization - Akilah, Rafa Nanda; Randolph, Bryant; Khawariz Andaristiyan, M. (Journal of physics. Conference series, 2024)
From the light curve taken during exoplanet transit, important parameters such as the radius ratio of the star-planet, impact parameter, inclination, and relative tangential velocity could be derived. A module was developed in the form of a Python library based on modeling using background simulation and fitting by utilizing global and local optimization, such as differential evolution and the Broyden–Fletcher–Goldfarb–Shanno (BFGS) method. For more accurate fitting, the effects of linear limb darkening on exoplanets are also included. The performance testing for the program was done by using dummy data to test its accuracy, followed by validation tests using WASP-12b transit curves to find out any discrepancies between our model and real exoplanet data. While performing a characterization test on WASP-12b, we found an interesting result regarding its impact parameter and the exoplanet’s velocity, which might be an interesting subject for further analysis.